Social policy, the media and misrepresentation - Franklin, Bob, 1949- (Routledge, 1999)
Social Policy, the Media and Misrepresentation examines aspects of news media reporting of social policy and how such coverage can influence processes of policy-making and implementation. It offers an appraisal of the complex inter-relationships between news media, news sources, the content of media coverage of social policy and its impact on audiences, public opinion and policy makers. Through detailed case studies, the various contributors explore: *social work and child protection *housing and homelessness *the charity and voluntary sectors *poverty and welfare policy *health (including HIV/AIDS) and mental health *education and crime and juvenile justice.